AN OVERVIEW OF DENGUE IN THE SOUTHERN REGION OF BRAZIL FROM 2001 TO 2017 - Andréia Dalla Vecchia; Vilma Beltrame; Fernanda Maurer D' Agostini (Universidade Federal do Paraná, 2018)
Objective:To record cases reported as classical dengue fever and deaths in the southern region of Brazil between 2001 and 2017. Method:Descriptive-retrospective study using secondary data from DATASUS/ SINAN and State Departments, analyzed through descriptive statistics. Results:An increase in the percentage of cases of the disease in the three states was observed in the three Brazilian southern states: in Paraná (PR) the percentage of autochthonous cases reached 94% in the last four years; in Santa Catarina (SC), the percentage was 95%, and in Rio Grande do Sul (RS), 83%, respectively, in 2015 and 2016. There was an increase in the number of deaths by severe dengue (dengue hemorrhagic fever), mainly in PR; in 2016, the first death caused by dengue was observed in SC; and an increase of more than 90% in the cases of dengue among adults in the last two years in Rio Grande do Sul. Conclusion:Despite the fact the Southern region of Brazil has the lowest incidence of dengue, special attention should be paid by health agencies to the situation in the southern states due to the increase in the number of cases and deaths caused by dengue.